Degradation During Emergencies: How the Pandemic Facilitated a State of Exception Within Canadian Prisons and Challenged Advocates to Become Hyper-Resilient - Blackwell, Emily (Université d'Ottawa / University of Ottawa, 2023)
Prisoner rights in Canada have historically been met with disrespect and disregard. Advocates have continuously fought for better protections of prisoner rights and legislation that bans the harmful treatment of prisoners. However, during the outbreak of the COVID-19 pandemic concerns arose about how prisoners’ rights were affected. Therefore, the question guiding this research is: How have the human rights of prisoners and (anti) carceral advocacy for their rights been impacted by the COVID-19 pandemic? To answer this question, a document analysis was conducted, using documents from academics who work in the field, government departments, and advocates working in a variety of areas. This thesis fills the gap in scholarly inquiry that the pandemic has created as the circumstances and the effects of the pandemic are unknown. The government reacted to the pandemic by implementing protocols that suited them with little regard for how prisoner rights could be affected, and neglected advocates recommendations for change. Advocates reacted by shifting their strategies to ensure they could continue advocating during the pandemic. The thesis revealed that during a crisis, both positive and negative reactions can co-occur. The pandemic created a state of exception within the penal system; therefore, an increase in rights violations occurred. However, an opportunity for positive change also emerged. Advocates used this opportunity to change their strategies and maintain their advocacy. By contrast, the government did not seize the same opportunity, as is evidenced by how the recommendations that advocates had been supporting were not implemented properly to protect prisoners.
Keywords: Covid-19; Human Rights; Prisons; Pandemic